Analysis of blood group antigens on MUC5AC in mucinous ovarian cancer tissues using in situ proximity ligation assay. (23rd August 2021) - Mateoiu, Constantina; Vitiazeva, Varvara; Kristjansdottir, Björg; Weijdegård, Birgitta; Örnros, Jessica; Gallini, Radiosa; Kamali-Moghaddam, Masood; Sundfeldt, Karin; Karlsson, Niclas G
Abstract: MUC5AC has been indicated to be a marker for mucinous ovarian cancer (OC). We investigated the use of in situ proximity ligation assay (PLA) for blood group ABH expressing MUC5AC to differentiate between serous and mucinous OC, to validate preceding observations that also MUC5AC ABH expression is increased in mucinous OC. We developed PLA for anti-A, B, and H/anti-MUC5AC and a PLA using a combined lectin Ulex europaeus agglutinin I (UEA I)/anti-MUC5AC assay. The PLAs were verified with mass spectrometry, where mucinous OC secretor positive patients' cysts fluids containing ABH O -linked oligosaccharides also showed positive OC tissue PLA staining. A nonsecretor mucinous OC cyst fluid was negative for ABH and displayed negative PLA staining of the matched tissue. Using the UEA I/MUC5AC PLA, we screened a tissue micro array of 410 ovarian tissue samples from patients with various stages of mucinous or serous OC, 32 samples with metastasis to the ovaries and 34 controls. The PLA allowed differentiating mucinous tumors with a sensitivity of 84% and a specificity of 97% both against serous cancer but also compared to tissues from controls. This sensitivity is close to the expected incidence of secretor individuals in a population. The recorded sensitivity was also found to be higher compared to mucinous type cancer with metastasis to the ovaries, where only 32% were positive. We conclude that UEA 1/MUC5AC PLA allows glycospecific differentiation between serous and mucinous OC in patients with positive secretor status and will not identify secretor negative individuals with mucinous OC.